Pengembangan E-Commerce Tembe Nggoli (Sarung) Khas Bima Berbasis Web Responsive di Desa Nata - Halilurahman Halilurahman; Evi Tandriani; I Ketut Putu Suniantara (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2021)
Tembe Nggoli is a typical Bima sarong made by weaving which is still preserved by the community in Neta Village, Palibelo District, Bima Regency. Tembe Nggoli is a hand-crafted art that has been passed down from generation to generation for the sake of preserving the weaving art. Currently, the selling process of Tembe Nggoli is still manual or conventional by selling directly to the public without marketing media so that it is only known by the surrounding community. This resulted in relatively lower income from the sale of Tembe Nggoli, so the process of returning capital was very slow. These problems can be solved by developing e-commerce in the sales process or introducing the craft. The purpose of this research is to build an e-commerce selling Tembe Nggoli based on a responsive website. The method used in building this application is the Software Development Life Cycle (SDLC) with the Waterfall Model. The results of this study have resulted in an e-commerce application selling the Tembe Nggoli Khas Bima sarong that is web-based responsive, so that the appearance of the application can adapt to various types of devices. With this application, it is expected to be able to provide convenience in the shopping process that can assist consumers in finding the desired product quickly and done anywhere and anytime. In addition, this application provides various kinds of information related to Tembe Nggoli products. Testing this system using blackbox testing which states that the system has been running in accordance with the functionality and procedures that are the purpose of developing the system. The functional suitability of the built system reaches 100%.